AB0001 Genetic Variants in IL-12B and IL-27 in The Patients with Systemic Lupus Erythematosus. (15th July 2016) - Paradowska-Gorycka, A.; Sowinska, A.; Stypinska, B.; Grobelna, M.; Walczyk, M.; Olesinska, M.; Piotrowski, P.; Jagodzinski, P.P.
Abstract : Background: Type-1 immunity plays a fundamental pathogenic role in various diseases including systemic lupus erythematosus (SLE), which is a multisystem autoimmune disorder with heterogeneity in clinical manifestations and disease course. Although the etiology and pathogenic mechanisms of SLE remains elusive, the actual state of knowledge allow diagnose that genetic information is important for understanding the mechanisms of the disorder. In this respect several studies support that gene encoding cytokines, which regulate CD4+T cells differentiation, are attractive genetic factors that may predispose to susceptibility and severity of SLE Objectives: To investigate the potential association between IL-12B and IL-27 gene polymorphisms and SLE, we performed a case-control study based on Polish population. Methods: SLE patients and healthy individuals, were examined for -6415 CTCTAA/GC (rs17860508) and +1188A/C (rs3212227) in IL-12B and -924A/G (rs153109) and 4730T/C (rs181206) in IL-27 gene polymorphisms using the HRM method, PCR–RFLP method and TaqMan SNP genotyping assay, respectively. Results: An increased frequency of GC/GC genotype as well as GC allele of the IL-12B rs17860508 was found in patients with SLE, as compared with healthy subjects (p<0.001). We did not find differences in genotype and allele frequencies of the IL-12B rs3212227 and IL-27 rs153109 and rs181206 variants between SLE patients and controls. IL-27 haplotype CG indicated higher risk for SLE (P=0.002), whereas haplotype TG indicated reduced risk for SLE (p=0.005). The IL-12B rs3212227 A/C polymorphism was associated with the mean value of the platelets, urea and complement C3 level. Furthermore IL-12B rs17860508 genetic variant showed correlation with platelets, prothrombin time, international normalized ratio and alkaline phosphatase. Conclusions: Our results revealed that IL-12B rs17860508 as well as IL-27 haplotype CG are genetic risk factors for SLE and that both IL-12B rs17860508 and rs3212227 predict disease phenotype. References: McCarthy EM, Smith S, Lee RZ, Cunnane G, Doran MF, Donnelly S et al. The association of cytokines with disease activity and damage scores in systemic lupus erythematosus patients. Rheumatology 2014; 53:1586–1594. Miteva LD, Manolova IM, Ivanova MG, Rashkov RK, Stoilov RM, Gulubova MV et al. Functional genetic polymorphisms in interlukin-12B gene in association with systemic lupus erythematosus. Rheumatol Int 2012; 32:53–59. Koening KF, Groeschl I, Pesickova SS, Tesar V, Eisenberger U, Trendelenburg M. Serum cytokine profil in patients with active lupus nephritis. Cytokine 2012; 60: 410–416. Guerra SG, Vyse TJ, Cunninghame Graham DS. The genetics of lupus: a functional perspective. Arthritis Res Ther. 2012;14(3):211. Acknowledgement: Supported by grant No 502–01–01124182–07474, Poznań University of Medical Sciences. The technical assistance of Mr. Agnieszka Hertel, Wieslawa Frankowska and Teresa Golaszewska is gratefully acknowledged. We are also grateful to all of the SLE patients whose cooperation made this study possible. Disclosure of Interest: None declared